Project on Human Development in Chicago Neighborhoods (PHDCN): Consequences of Substance Use, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Consequences of Substance Use interview. It was administered to subjects in Cohorts 9, 12, 15, and 18 and obtained information related to outcomes of the subject being caught, by school officials, police, or their parents, using alcohol or drugs. Subjects in Cohorts 15 and 18 were asked questions from a slightly different instrument than subjects in Cohorts 9 and 12. Cohorts 15 and 18 were asked more detailed questions regarding what substances and what quantity subjects were caught with.